Simple Mechanical Beneficiation Method of Coarse Fly Ash with High LOI for Making HVFA Mortar - Antoni ,; Vindy Satrya; Djwantoro Hardjito (Civil Engineering Dimension, 2015)
This study focusses on the effect of milling of fly ash obtained from four different sources on the properties of high volume fly ash (HVFA) mortar. Two fly ash samples with low loss-on-ignition (LOI) were taken from a coal-fired power plant, while the other two with high LOIs were obtained from a textile factory and from a paper mill, respectively. Milling was performed using a rod mill at a certain period of time. The workability of HVFA mortar with constant water to cementitious ratio was controlled by adjusting the superplasticizer content. The results show that the specific gravity of fly ash increases after milling. Utilizing milled fly ash ends up with significant strength increase of HVFA mortar, especially those utilizing high LOI fly ash. This shows that milling is an excellent fly ash beneficiation technique, especially on the one with high LOI value.